Desarrollo de estrategias de Marketing Digital para el posicionamiento del Complejo Turístico Altamira, cantón Echeandía, provincia Bolívar, año 2019 - Borja Zurita, Wiliam Patricio (2019)
The purpose of this research is to improve the positioning of the Altamira de Echeandía Tourist Complex through the application of digital marketing strategies; generating content on the virtual platforms of the company taking advantage of its tourist attractions. All this with the objective of informing, communicating and persuading users; In this way, the company also increases its client portfolio. During the investigation process, the shortcomings were identified, the main one being the lack of content generation in the company's digital media; in addition to not having a multichannel in terms of digital platforms, which is why the design of a digital marketing plan with the development of digital strategies is proposed; In addition to the creation of missing social networks. Another of the shortcomings of the company is to apply empirical management in terms of digital planning. In the execution of this project, the quality of content published on the social networks of the establishment has been improved, as well as having greater frequency in them, thus creating continuous interactivity with users and keeping them updated with the company's services and news. This research contributed to better management in terms of digital planning by the administration, as well as improving the company's communication and increasing brand positioning. Descriptive Terms: Digital marketing, digital content, digital advertising, digital strategies, Tourism marketing.